Predictive Risk Factors of Intestinal Necrosis in Patients with Mesenteric Venous Thrombosis: Retrospective Study from a Single Center. (7th May 2019) - Wang, Yong; Zhao, Rui; Xia, Lin; Cui, Ya-Ping; Zhou, Yong; Wu, Xiao-Ting
Abstract : Purposes . Mesenteric venous thrombosis (MVT) is a serious condition. The current study aimed to identify risk factors of intestinal necrosis (IN) in patients with MVT to predict the onset of patients. Methods . Data pertaining to patients diagnosed with MVT between 2014 and May 2018 were reviewed. Patients' characteristics and risk factors of IN were assessed. Results . Seventy-eight patients were included in our study, of whom all cases were diagnosed as superior mesenteric venous thrombosis. There were fifty-eight cases (74%) with intestinal necrosis and twenty cases (26%) without intestinal necrosis. Multivariate analysis of factors associated with IN was organ failure (odds ratio (OR): 4.1; 95% confidence interval (95%CI): 1.26–8.59; P =0.028), elevated serum lactate (OR:3.6; 95% CI: 1.51–5.47; P =0.024), bowel loop dilation on computerized tomography (CT) scan (OR: 2.8; 95% CI: 1.32–7.23; P =0.031), and the time between onset of symptoms and operation (OR: 4.8; 95% CI: 1.36–9.89; P =0.012). Area under the receiver operating characteristics curve for the diagnosis of IN with MVT was 0.901 (95%CI: 0.809–0.993; P=0.000) depending on the different number of predictive factors. Conclusion . Predictive risk factors for IN with MVT were organ failure, elevated serum lactate level, bowel loop dilation on CT, and the time between onset of symptoms and operation. However, this result is from a retrospective study and further long-term, large-sample prospective studies are required to confirm this finding.